2016
DOI: 10.1144/sp448.6
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting microfossil preservation and lake chemistries within the 1200–1000 Ma Torridonian Supergroup of NW Scotland

Abstract: Oxygenation of the Proterozoic atmosphere caused the progressive build-up of dissolved sulphate on the continents and in marine environments. However, oxygen levels in the Proterozoic were low enough to allow the early burial of biological material into low redox potential environments where permineralization and the authigenic replacement of organic material, including micro-organisms, occurred by a range of minerals. Consequently, microbial sulphate reduction caused the widespread degradation of organic matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…These data add to recent studies that report concentrations of elements indicative of clays (e.g. aluminium and iron) adjacent to other Proterozoic fossils [21][22][23]. The organisms studied here probably represent a variety of evolutionary clades, including eukaryotic chlorophyte algae and cyanobacteria [24][25][26][27]29].…”
Section: Kaolinite and Proterozoic Fossilizationsupporting
confidence: 68%
See 1 more Smart Citation
“…These data add to recent studies that report concentrations of elements indicative of clays (e.g. aluminium and iron) adjacent to other Proterozoic fossils [21][22][23]. The organisms studied here probably represent a variety of evolutionary clades, including eukaryotic chlorophyte algae and cyanobacteria [24][25][26][27]29].…”
Section: Kaolinite and Proterozoic Fossilizationsupporting
confidence: 68%
“…Intriguingly, elements indicative of these clays (e.g. aluminium and iron) have also been reported adjacent to some Proterozoic fossils, but their host phases are difficult to constrain [21][22][23]. Do aluminium-and/or iron-rich clay minerals promote fossilization in Proterozoic strata?…”
Section: Introductionmentioning
confidence: 99%
“…5g, h). These data indicated that different suites of lakes within the Torridonian had different chemistries, with those of the Stoer Group being sulphate-rich and phosphate-poor compared with those of the Cailleach Head and Diabaig formations (for further details on contrasting fossil preservation in these lakes, see Wacey et al 2016).…”
Section: Colour Online/ Colour Hardcopymentioning
confidence: 98%
“…STEM‐EDS maps plus extracted spectra reveal it is made of Ti and O (Figure 3b,e), and electron diffraction in the TEM shows it is the TiO 2 phase anatase (Figure 3d). Other surrounding mineral phases such as francolite, and iron–magnesium‐rich and potassium‐rich clay minerals are identified via EDS spectra and mapping, and with comparison to previously published work (Wacey, Battison, Garwood, Hickman‐Lewis, & Brasier, 2016; Wacey, Brasier, et al, 2016; Wacey et al, 2014, 2019).…”
Section: Resultsmentioning
confidence: 82%